Pengaruh E-Commerce dan Pendidikan Kewirausahaaan Syariah Terhadap Minat Berwirausaha pada Mahasiswa - Afifah Putri Wardana; Abiyajid Bustami (Al-Musthofa: Journal of Sharia Economics, 2025)
The high unemployment rate among Generation Z in Indonesia has created an urgency to promote entrepreneurship as an alternative solution, particularly through the utilization of e-commerce and Sharia entrepreneurship education. This study aims to determine the influence of e-commerce and entrepreneurship education on entrepreneurial interest among Sharia Economics students at Mulawarman University who utilize e-commerce and have taken the entrepreneurship course. This research employs a quantitative method. Data were collected via a questionnaire using Google Forms. The data analysis techniques include testing the validity and reliability of the instrument, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple linear regression analysis with hypothesis testing through partial t-tests. The results show that the e-commerce variable has a positive and significant effect on entrepreneurial interest. Likewise, the Sharia entrepreneurship education variable is proven to have a positive and significant influence on students’ entrepreneurial interest. This indicates the importance of integrating technology and Sharia entrepreneurial values in shaping independent and ethical entrepreneurial character.